Valuing climate protection by offsetting carbon emissions: rethinking environmental governance - Rafia, Afroz (Elsevier Inc., 2014)
This study aimed to investigate households’ willingness to pay (WTP) for a carbon reduction programme, the demographic and socioeconomic factors that influence households’ WTP. The contingent valuation method (CVM) was employed as a mechanism to decide a monetary valuation of public preferences for offsetting carbon emissions by ascertaining the value attached to climate protection in Kuala-Lumpur, Malaysia. The valuation of public preference was measured by the households’ WTP for a specific amount of climate protection. This study found that approximately 71% of households were WTP towards the protection of the climate (better environment). The findings validated that socioeconomic variables, such as education, income, acquired awareness and knowledge of climate change issues have significant impacts on WTP and the mean WTP is MYR15.38 (US$1= MYR3.25) monthly. However, WTP varied considerably with household perception of the value of climate protection. This study would be useful in designing an appropriate policy framework fostering new policy-oriented sustainability and further carbon footprint research.